Analysis of Tarkib Idhofi in the Qur’an Surah Annisa’ (Learning Nahwiyah) | Analisis Tarkib Idhofi dalam al-Qur’an Surat Annisa’ (Pembelajaran Nahwiyah) - Fatkhur Roji; Muhammad Syaifullah; Mohammad Izdiyan Muttaqin (Mantiqu Tayr: Journal of Arabic Language, 2021)
Surah Annisa’ is very popular and is often used as material for preaching and determining the study of women, but often researchers find errors in the interpretation and understanding of conveying the verses in the Annisa’ letter, these errors are found in understanding the verses that contain tarkib idhofy, which should be destined في , conveying to be ل, the purpose of this study is to minimize misunderstanding and provide insight into the study of tarkib idhofy. This study uses a research library research design, the data in this study is the Idhofy tag which is contained in Annisa's letter. The results of the study stated that those who have tarkib idhofy in Annisa verses 1 to 25, have tarkib idhofy, the verses are in verses 1, 2, 4, 6, 7, 9, 10, 11, 12, 13, 15, 16, 20, 23, 24, and 25. And from the results of the semantic analysis, it is stated that the meaning of min (من) has 8 lafadz, while those that have the meaning fii (في) are 4 lafadz, and those which have the meaning of ownership (ل) are 13 lafadz.